(untitled) (Mustansiria Dental Journal, 2018)
This study aimed to determine the sagittal lip position and some of the factors affecting it regarding the gender differences, and their correlations in a sample of Iraqi adults. Sixty two participants (37 females and 25 males) collected among dental students having Cl I skeletal and occlusal relations and full permanent dentition regardless the third molars were chosen for this study. Each person was subjected to clinical examination and digital true lateral cephalometric radiograph. The radiographs were analyzed by using AutoCAD 2007 computer program to measure the sagittal lip position using the soft tissue analyses of Steiner, Burstone, Ricketts, Sushner, Holdaway, and Merrifield. Descriptive statistics were obtained from the measurements of both genders; independent samples t-test was performed to evaluate the gender differences and Pearson’s correlation coefficient test was used to find the contributing factors to the sagittal lip position. Sagittal jaw angles were significantly higher in males than females, while vertical jaw angle was higher in females. Lower incisors showed slight proclination in both genders. The mean values of H-angle and revised H-angle in males were nonsignificantly higher than that of females, while the mean value of Z-angle was nonsignificantly higher in females. Upper and lower lips thickness mean values were significantly higher in males. Females had non-significantly more projected nose compared to males. Regarding the sagittal lip position, upper and lower lip measurements were non-significantly higher in males than females in Ricketts, Steiner, Burstone, and Holdaway analyses, but it was significant in Sushner analysis, while Z-angle of Merrilfield was non-significantly higher in female sample. Pearson’s correlation coefficient test revealed that upper and lower lip thickness was significantly positively correlated with sagittal lip position, while nose projection was significantly negatively correlated. Sagittal position values of the upper and lower lips in a sample of Iraqi adults are close to the norms of Ricketts, Steiner, Sushner, Burstone, and Holdaway analyses with a slight tendency of upper lip toward retrusion and lower lip toward protrusion with the exception of that when compared with Sushner norms. In addition to the chin position, lips thickness and nose projection are the most important factors that influence the sagittal lip position and compensate for the variations in the jaw bases between genders.